2020
DOI: 10.21577/0103-5053.20190228
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion 3D Printed Composite with Multifunctional Applications for Tissue Engineering and Photodynamic Therapy

Abstract: Upconversion nanoparticles (UCNPs) are suitable materials for bioapplications due to their ability to emit visible light under near infrared (NIR) excitation, in the biological transparency range. Polycaprolactone(PCL)-based scaffolds are widely used in tissue engineering in combination with inorganic compounds to improve bioactivity and osteoconductive properties. This work proposes a 3D printed composite scaffold with upconversion property aiming at biomedical applications in therapy-stimulated bone repair a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Nigoghossian et al [121] focused on evaluating the cytotoxicity, genotoxicity, and mutagenicity of UCNPs incorporated into a 3D-printed composite scaffold with upconversion luminescence for potential biomedical applications. Their system combined the polymer PCL, UCNPs-apatite, and a photosensitizer for PDT in stimulating bone repair.…”
Section: Cellular Localization Of Fluorescence Y2o3:eu 3+ -Fa Nanopar...mentioning
confidence: 99%
“…Nigoghossian et al [121] focused on evaluating the cytotoxicity, genotoxicity, and mutagenicity of UCNPs incorporated into a 3D-printed composite scaffold with upconversion luminescence for potential biomedical applications. Their system combined the polymer PCL, UCNPs-apatite, and a photosensitizer for PDT in stimulating bone repair.…”
Section: Cellular Localization Of Fluorescence Y2o3:eu 3+ -Fa Nanopar...mentioning
confidence: 99%
“…PS-PCL/UCNPs-apatite composite produced singlet oxygen and displayed PDT properties while the 3D printed scaffold had no effect on optical properties. 50 However, PCL/UCNPs-apatite is genotoxic and mutagenic toward CHO-K1 cells at higher concentrations of rare earth elements and can currently only be used at lower biosafe concentrations.…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 99%
“…Nigoghossian et al developed UCNP-based scaffolds for photodynamic therapy (PDT) under 980 nm excitation. 140 Here, UCNPs were used as a transducer to initiate a photosensitizer (erythrosine B) in polymerization. When 12.5 wt% UCNPs and erythrosine B are embedded into polymeric materials using FDM technology, a proof-of-concept study confirmed that fabricated scaffolds could generate cytotoxic singlet oxygen under NIR excitation, inducing cell apoptosis.…”
Section: Upconversion Nanoparticles (Ucnps)mentioning
confidence: 99%